2010
DOI: 10.1111/j.1365-2141.2010.08340.x
|View full text |Cite
|
Sign up to set email alerts
|

Weekly versus twice weekly bortezomib given in conjunction with rituximab, in patients with recurrent follicular lymphoma, mantle cell lymphoma and Waldenström macroglobulinaemia

Abstract: SummaryThe combination of bortezomib and rituximab was evaluated in patients with mantle cell lymphoma (MCL), follicular lymphoma (FL) and Waldenström macroglobulinaemia (WM), in a Phase I and later, a randomized Phase II study. In the randomized study, 42 patients with recurrent/refractory disease received either: bortezomib 1AE3 mg/m 2 on days 1, 4, 8 and 11 of a 3-week cycle with rituximab 375 mg/m 2 on day 1 (21 patients) or: bortezomib 1AE6 mg/m 2 and rituximab on days 1, 8, 15 and 22 of a 5-week cycle (w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 50 publications
(67 reference statements)
2
39
0
Order By: Relevance
“…Bortezomib may not only be combined with rituximab, 37,39 but also with cytarabine, 40 fludarabine, 41 and even polychemotherapy. 42 Although the actual numbers of MCL patients in trials of such combinations are very small, the combinations do appear to have greater efficacy compared to bortezomib alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bortezomib may not only be combined with rituximab, 37,39 but also with cytarabine, 40 fludarabine, 41 and even polychemotherapy. 42 Although the actual numbers of MCL patients in trials of such combinations are very small, the combinations do appear to have greater efficacy compared to bortezomib alone.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropathy also developed frequently in a recent trial of bortezomib in MALT lymphoma, in which the dose of bortezomib was 1.5 mg/m 2 administered twice weekly. 38 Besides the early dose modification of bortezomib, alternative doses and schedules of bortezomib should be considered in lymphoma patients, 39 in particular if bortezomib is used after prior administration of neurotoxic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized comparisons generally reported similar efficacies for the twice-weekly schedule and the once-weekly schedule [100,108,119,121,159,160]. But, as noted above, weekly dosing of bortezomib in combination regimens led to better tolerability than with the twice-weekly dosing schedule in some of those studies [108,121,159,160]. In our practice, we typically administer bortezomib as a single agent, either i.v.…”
Section: Dosingmentioning
confidence: 99%
“…Some studies have suggested that weekly dosing of bortezomib (instead of twice weekly) in combination regimens may improve tolerability [108,121,159,160].…”
Section: Tolerabilitymentioning
confidence: 99%
“…Rituximab, 7 chlorambucil, 8 alkylating agent combinations, 9 R-CHOP (rituximab, CY, doxorubicin (hydroxydaunorubicin), VCR (Oncovin) and prednisone) 10,11 and purine nucleoside analogs 12,13 have all produced high response rates, and many of the responses are durable. Recently, bortezomib 14,15 and bendamustine 16 have both been shown to be highly active in the management of Waldenströ m macroglobulinemia. Investigations into the use of the mTOR inhibitor everolimus 17 have shown it to be useful in heavily pretreated Waldenströ m macroglobulinemia.…”
Section: Why Consider a Transplant In This Disease?mentioning
confidence: 99%